Intrapulmonary Pharmacokinetics of Laninamivir, a Neuraminidase Inhibitor, after a Single Nebulized Administration of Laninamivir Octanoate in Healthy Japanese Subjects - Toyama, Kaoru; Furuie, Hidetoshi; Ishizuka, Hitoshi (Antimicrobial Agents and Chemotherapy, 2018)
A single dose of laninamivir octanoate (LO) inhaled using a dry powder inhaler (DPI) is effective for the treatment and prophylaxis of influenza. Nebulizers are an option for pediatric and elderly patients who may have difficulty in using a DPI. A single-center, open-label study was conducted to evaluate the plasma and intrapulmonary pharmacokinetics (PK) of laninamivir after a single nebulized administration of LO in healthy male Japanese subjects for identifying a safe and effective dosage regimen for a nebulizer. A single dose of LO (40 to 320 mg) was administered using a nebulizer, and plasma concentrations of LO and laninamivir were analyzed up to 168 h after inhalation by validated liquid chromatography-tandem mass spectrometry methods. Subgroups of 6 subjects each underwent bronchoalveolar lavage at specified time intervals over 4 to 168 h following a single nebulized administration of LO (160 mg), and the concentrations in epithelial lining fluid (ELF) were calculated by the urea diffusion method. PK parameters were determined by noncompartment analysis. Inhaled nebulized LO was found to be safe and well tolerated up to the highest dose evaluated (320 mg). Plasma laninamivir concentrations increased almost dose proportionally. Laninamivir concentrations in ELF exceeded the 50% inhibitory concentrations for viral neuraminidase up to 168 h after the nebulized inhalation of 160 mg LO. Thus, similarly to the DPI, ELF concentration profiles of laninamivir after a single nebulized administration support its long-lasting effect against influenza virus infection. This study has been registered at JAPIC Clinical Trials Information ( http://www.clinicaltrials.jp/ ) under registration no. JAPIC CTI-152996.